Porcine, bovine, and mixed gelatin identification using SPME-GC-MS and chemometrics - Darmawan, Noviyan; Sari , Intan Dias; Rudhatin, Fayca; Pranata, Agy Wirabudi; Supratikno; Yuliana, Nancy Dewi (IPB University, 2024)
Gelatin is a versatile raw material extensively used in the food, cosmetics, and pharmaceutical industries. It is produced globally by partially hydrolyzing collagen derived from pigs and cows, leading to religious and ethical concerns among various communities. Therefore, this study aimed to explore alternative methods to distinguish porcine, bovine, and mixed gelatin by analyzing the unique profiles of their total volatile compounds. The volatilomics method integrated solid-phase microextraction gas chromatography-mass spectrometry (SPME-GC-MS) with chemometrics. The results showed that principal component analysis (PCA) of the volatile compounds from gelatin powder had clear classification among porcine, bovine, and mixed gelatin, suggesting the discrimination ability of the method. Furthermore, partial least squares discriminant analysis (PLS-DA) identified distinct marker compounds that significantly contributed to the classification of each gelatin type. The marker compounds for porcine gelatin included 2-decen-1-ol, 2-dodecenal, cyclohexane 1-butenylidene, decane 3,6-dimethyl, cyclohexanone 2-propyl, borinic acid, 3-tetradecyn-1-ol, 2-tridecene, 5,5-dimethyl-1,3-dioxan-2-one, and 2-n-butyl furan. For bovine gelatin, the marker compounds were 2-heptanone 3-methyl, nonane 5-butyl, tridecane 6-methyl, 1-hexacosanol, nonane 3-methyl-5-propyl, undecane 3-methyl, octane 4-methyl, 2,4-undecadienol, and 1-hexadecanol 2-methyl.